2019
DOI: 10.1073/pnas.1903896116
|View full text |Cite
|
Sign up to set email alerts
|

An endosomal LAPF is required for macrophage endocytosis and elimination of bacteria

Abstract: Macrophages can internalize the invading pathogens by raft/caveolae and/or clathrin-dependent endocytosis and elicit an immune response against infection. However, the molecular mechanism for macrophage endocytosis remains elusive. Here we report that LAPF (lysosome-associated and apoptosis-inducing protein containing PH and FYVE domains) is required for caveolae-mediated endocytosis.Lapf-deficient macrophages have impaired capacity to endocytose and eliminate bacteria. Macrophage-specificLapf-deficient mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Recently, some biomacromolecules and polymers without aromatic rings, including protein fibrils, polypeptides, poly(amido amine)s (PAMAMs), polyethylenimine (PEI), hyperbranched poly(amino ester), and polyurea dendrimers, were reported to possess remarkable fluorescence in the aggregated state and in solution, confirming that aromatic groups are not the basic requirement for photoluminescence. Accordingly, some other mechanisms have been proposed, such as cluster‐triggered emission, aggregation‐induced emission (AIE), crosslink‐enhanced emission (CEE), and so on. Regardless of the different names, these mechanisms are mainly related to the interactions of polymer chains or molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some biomacromolecules and polymers without aromatic rings, including protein fibrils, polypeptides, poly(amido amine)s (PAMAMs), polyethylenimine (PEI), hyperbranched poly(amino ester), and polyurea dendrimers, were reported to possess remarkable fluorescence in the aggregated state and in solution, confirming that aromatic groups are not the basic requirement for photoluminescence. Accordingly, some other mechanisms have been proposed, such as cluster‐triggered emission, aggregation‐induced emission (AIE), crosslink‐enhanced emission (CEE), and so on. Regardless of the different names, these mechanisms are mainly related to the interactions of polymer chains or molecules.…”
Section: Introductionmentioning
confidence: 99%
“…These changes depend on the intermolecular distances, and the orientation of dye molecules and are the result of electrostatic interactions between the transition moments . The planar structural features of common xanthene derivatives facilitate π‐π interaction between the dye molecules, which also interact through various other interactions (e. g. inter or intra molecular charge transfer, energy transfer and excited state reactions), resulting in aggregation caused quenching (ACQ) . Thus, low Rh6G emission at 0 min could be attributed to the fact that Rh6G particles freshly scattered on the PSpBSA liq were in aggregated state (as seen in POM data in Figure e and 2f), resulting in a quenched emission intensity (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Our lab previously found that Siglec-G negatively regulated cross-presentation in DCs through SHP1. We recently found that Src-LAPF-Cav1 promoted both bacteria and TLR4 endocytosis (37), which indicated that activating Src might increase anti-bacterial innate immunity. Further studies on Siglec-G in different cells by regulating SHP1/2 and Src activation may reveal the molecular mechanism of innate immune responses.…”
Section: Discussionmentioning
confidence: 99%